2019
DOI: 10.1039/c8ra08857h
|View full text |Cite
|
Sign up to set email alerts
|

Photo-enhanced gas sensing of SnS2 with nanoscale defects

Abstract: A photon assisted SnS2-based gas sensor with an ultra-high sensitivity of 3 ppb NO2 has been achieved at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 58 publications
4
35
0
Order By: Relevance
“…The SnX 2 (X = S, Se)-based gas sensors show a good response to NO 2 at room temperature [6][7][8]. Furthermore, the SnSe 2 monolayer shows a higher sensitivity for NO 2 molecule adsorption than SnS 2 in our related work [7,8]. Also, the charge transfers and the flat band contributed by gas adsorption induces the conductivity difference of the SnSe 2 monolayer reported in our previous study [8].…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…The SnX 2 (X = S, Se)-based gas sensors show a good response to NO 2 at room temperature [6][7][8]. Furthermore, the SnSe 2 monolayer shows a higher sensitivity for NO 2 molecule adsorption than SnS 2 in our related work [7,8]. Also, the charge transfers and the flat band contributed by gas adsorption induces the conductivity difference of the SnSe 2 monolayer reported in our previous study [8].…”
Section: Introductionsupporting
confidence: 50%
“…The layered SnX 2 (X = S, Se) nanosheets show a significant sensitivity to individual molecules, such as NO 2 and NH 3 [3,[6][7][8]. The SnX 2 (X = S, Se)-based gas sensors show a good response to NO 2 at room temperature [6][7][8]. Furthermore, the SnSe 2 monolayer shows a higher sensitivity for NO 2 molecule adsorption than SnS 2 in our related work [7,8].…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Zhang et al have demonstrated a self-assembled SnS 2 nanoflower/Zn 2 SnO 4 hollow sphere nanohybrid device, exhibiting excellent humidity sensing properties 20 . Recently, Yan et al fabricated NO 2 gas sensor based on CVD grown SnS 2 with ultra-high sensitivity by utilizing inherent defects under photoillumination 21 . Although, there are many reports on SnS 2 based devices for humidity and gas sensing, the quest is always on for fabrication of devices with properties such as large area with simple designs, self-powered, ultrasensitive and room temperature humidity sensing.…”
mentioning
confidence: 99%
“…There are several techniques to obtain low-dimensional SnS 2 thin films. Exfoliation, chemical vapour deposition (CVD), hydrothermal and solvothermal synthesis, and sputtering have been extensively used for fabricating nanofilm based devices [20][21][22][23][24] . However, exfoliation of nanoflakes and growth of thin films by CVD result in thin films whose sizes are in the range of few μm, thus hindering the large-scale growth optimum for industrial scale applications.…”
mentioning
confidence: 99%